Digital Gold Installment Innovation at Bank Muamalat: Sharia Compliance and Digital Accessibility - Adlha, Wafiroh Dwi; Ekaningsih, Lely Ana Ferawati (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study analyzes the innovation of the digital gold installment product Solusi Emas Hijrah (SOLEH) at Bank Muamalat, focusing on sharia compliance and accessibility. The background highlights the rapid growth of Islamic fintech in Indonesia alongside persistent public doubts about the permissibility of digital gold installment transactions and weaknesses in the implementation of the Rahn contract. The objective is to understand how digital innovation is integrated, how sharia compliance is executed, and how accessibility is perceived by customers. A qualitative case study approach was employed at Bank Muamalat’s Genteng sub branch in Banyuwangi. Data were collected through in depth interviews with the branch manager, funding officer, and two customers, supported by observation and documentary studies. The findings reveal that the product successfully integrates digital convenience through the Muamalat DIN application with the security of physical gold ownership using Murabahah and Rahn contracts, offering high financing limits up to 500 grams and a tenor of 10 years. Sharia compliance is implemented through rigorous verification, customer education, and price transparency. However, the Rahn contract still shows weaknesses in asset ownership clarity. Accessibility encompasses three interrelated dimensions: digital, economic (installment affordability is more valued by customers), and cognitive (low public understanding remains the greatest challenge). The study concludes that the success of Islamic fintech depends not merely on technological innovation but on tangible sharia compliance and addressing fundamental financial needs.